Health seeking behaviors and maternal and child health outcomes: Case of Ata-Matigsalug and Non-Ata-Matigsalug adolescent mothers in Davao Region, Southern Philippines - Pelayo, Mary Grace A. (Animo Repository, 2015)
Adolescent pregnancy is among the myriad of issues encountered by many developing teens. This study compared and described the socio-demographic characteristics, pregnancy intention, and cultural beliefs and practices on pregnancy of the Ata-Matigsalug and non-Ata Matigsalug adolescent mothers in Davao region, Southern Philippines. It also described the health seeking behaviors of early childbearing adolescent mothers and its linkage to the health outcomes of both the mother and the child. This study is quantitative in nature and utilized the survey method via face-to-face interview with 67 adolescent mothers chosen through non-probability sampling. Results of the study revealed that the Ata-Matigsalug adolescent mothers are relatively disadvantaged compared to their non-Ata-Matigsalug counterparts in accessing health care facilities, skilled birth attendants, and formal medical services, specifically in terms of being assisted by skilled birth attendants in child delivery. This is because most of these indigenous mothers are living below the country's poverty threshold and are situated far from a health facility. Thus, despite a good record of ante-natal care (ANC) visits in health centers, birth delivery of the Ata-Matigsalug mothers were still primarily assisted by traditional birth attendants. A reason for this is that ante-natal services are free in public or government facilities unlike access to formal medical services on child delivery. Another reason is that Ata-Matigsalug mothers living far from a health facility are faced not only by the costs of transportation but also by the danger to their lives and their children's in travelling considerable distances to give birth in a health facility. The study shows a trend on the adolescent mothers civil status, household income, and proximity to a health service facility to their health seeking behaviors among the significant variables. Frequency of antenatal visits of the non-Ata-Matigsalug mothers was revealed to be significantly related to their health outcomes. Moreover, the prenatal health seeking behavior of the adolescent mothers was found to have significant association with the health outcomes of their children. In other words, the well-being of children is deeply linked to the health of their mothers.